2011
DOI: 10.3892/or.2010.1084
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin sensitizes human hepatocellular carcinoma cells, but not hepatocytes and mesenchymal stem cells, to TRAIL within a therapeutic window partially depending on the upregulation of DR5

Abstract: Abstract. Tumor necrosis factor (TNF)-related apoptosisinducing ligand (TRAIL) is a member of the TNF family of cytokines and has been shown to induce cell apoptosis in many types of tumors, but not in normal cells. This tumorselective property has made TRAIL a promising approach for the development of cancer therapy. However, hepatocellular carcinoma (HCC) cells display a striking resistance to TRAIL. Although some chemotherapeutic agents can overcome this resistance, safety issues remain a concern because th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…As a more general phenomenon, it has been suggested that MSCs can escape apoptotic induction also after exposure to various other anti-cancer agents 27 , 30 , 34 . The observation of low apoptosis induction in MSCs has been attributed to an impaired p73-dependent activation of pro-apoptotic proteins, an inhibition of the TRAIL pro-apoptotic pathway and strong constitutive expression of several anti-apoptotic factors like Bcl-2 and Bcl-xL 35 37 . In our dataset, MSCs exhibited strong increases in senescence-associated β-galactosidase stainings even after low doses of paclitaxel; this may explain the observed inactivation of cellular proliferation in taxane-treated MSCs while preserving their metabolic viability.…”
Section: Discussionmentioning
confidence: 99%
“…As a more general phenomenon, it has been suggested that MSCs can escape apoptotic induction also after exposure to various other anti-cancer agents 27 , 30 , 34 . The observation of low apoptosis induction in MSCs has been attributed to an impaired p73-dependent activation of pro-apoptotic proteins, an inhibition of the TRAIL pro-apoptotic pathway and strong constitutive expression of several anti-apoptotic factors like Bcl-2 and Bcl-xL 35 37 . In our dataset, MSCs exhibited strong increases in senescence-associated β-galactosidase stainings even after low doses of paclitaxel; this may explain the observed inactivation of cellular proliferation in taxane-treated MSCs while preserving their metabolic viability.…”
Section: Discussionmentioning
confidence: 99%
“…This resistance against apoptotic activation has been reported after other forms of cytotoxic treatment 37 , and it has been suggested that the observed resistance of MSCs is due to a reduced p73-dependent activation of pro-apoptotic proteins, p21 and Bax and high constitutive expression levels of various anti-apoptotic proteins such as Bcl-2 and Bcl-xL 38 39 . Additionally, MSCs were shown to lack activation of the TRAIL pro-apoptotic pathway upon cisplatin treatment 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these studies provide also the molecular mechanisms underlying the ability of these drugs to enhance TRAIL sensitivity (Table 2). In particular, cisplatin and 5-FU trigger the downregulation of the antiapoptotic proteins cFLIP and the upregulation of TRAIL - R1 and TRAIL-R2 receptors and may efficiently sensitize HCC cells, but not normal hepatocytes to TRAIL-induced apoptosis [28,60]. Conversely the synergistic effect of TRAIL and etoposide, does not rely on the increase of the expression of TRAIL receptors, but rather is associated with the amplification of the mitochondrial signal pathway [61].…”
Section: Development Of Trail-based Combined Therapeutic Approachementioning
confidence: 99%